How Do Science Communication Practitioners View Scientists and Audiences in Relation to Public Engagement Activities? A Research Note Concerning the Marine Sciences in Portugal - Lourenço Pinto, Bruno Miguel (2020)
This exploratory study is focused on the perceptions of science communication practitioners about the activities of scientists and the audiences of the marine sciences outreach in Portugal. Using the qualitative method of thematic analysis and collecting data through semistructured interviews of 14 practitioners of diverse professions, backgrounds, ages, and stages of career, it was found that the role of marine scientists in this area is traditionally viewed as reduced, but with a slight improvement in the past 5 to 10 years. Despite having a historical connection with and curiosity about the sea, audiences were considered to have a mostly utilitarian interest in the marine sciences. Most practitioners had a view of science communication connected to the knowledge deficit model, with a minority articulating a more dialogical model. Although there are signs of conflict between science communicators and scientists, the proliferation of training opportunities in science communication at the national level, the perceived increase of interest and participation of marine scientists in public communication in the past years, and the consolidation of science communicators as part of the scientific community offer positive prospects for the future of outreach of marine sciences in Portugal.